Hybrid End-to-End VPN Security Approach for Smart IoT Objects - Juma a, Mazen (2020)
The End-to-End VPN security has an essential role especially in connecting smart objects in the Internet of Things (IoT) environments. It noted that security is a crucial issue in the End-to-End VPN approach. IPSec/IPv6 and OpenSSL are the most common VPN approaches used separately to secure smart IoT objects in different envi ronments. These approaches have strengths and weaknesses. This paper addresses the development of a Hybrid End-to-End VPN security approach achieved by combining the IPSec/IPv6 and OpenSSL security approaches that can secure smart IoT objects in different settings. This proposed solution achieves the best combinations of complementary advantages of IPSec/IPv6 VPN approach and OpenSSL VPN approach and eliminates their shortcomings. Performance evaluation of the proposed Hybrid approach and the analysis of the comparison outputs of the performance of both IPSec/IPv6 VPN and OpenSSL VPN approaches assessed in terms of a group of standard measurements, for example, throughput, round-trip delay, and bandwidth consumption. The results of the simulation for the proposed solution demonstrate the correlation with acceptance levels compared to IPSec/ IPv6 VPN, and OpenSSL VPN approaches.